Investigation of the absolute bioavailability and human mass balance of navoximod, a novel IDO1 inhibitor. Issue 8 (14th June 2019) - Ma, Shuguang; Suchomel, Julia; Yanez, Evelyn; Yost, Edward; Liang, Xiaorong; Zhu, Rui; Le, Hoa; Siebers, Nicholas; Joas, Lori; Morley, Roland; Royer‐Joo, Stephanie; Pirzkall, Andrea; et al.
Abstract : Aims: Navoximod (GDC‐0919, NLG‐919) is a small molecule inhibitor of indoleamine‐2, 3‐dioxygenase 1 (IDO1), developed to treat the acquired immune tolerance associated with cancer. The primary objectives of this study were to assess navoximod's absolute bioavailability (aBA), determine the mass balance and routes of elimination of [ 14 C]‐navoximod, and characterize navoximod's metabolite profile. Methods: A phase 1, open‐label, two‐part study was conducted in healthy volunteers. In Part 1 (aBA), subjects ( n  = 16) were randomized to receive oral (200 mg tablet) or intravenous (5 mg solution) navoximod in a crossover design with a 5‐day washout. In Part 2 (mass balance), subjects ( n  = 8) were administered [ 14 C]‐navoximod (200 mg/600 μCi) as an oral solution. Results: The aBA of navoximod was estimated to be 55.5%, with a geometric mean (%CV) plasma clearance and volume of distribution of 62.0 L/h (21.0%) and 1120 L (28.4%), respectively. Mean recovery of total radioactivity was 87.8%, with 80.4% detected in urine and the remainder (7.4%) in faeces. Navoximod was extensively metabolized, with unchanged navoximod representing 5.45% of the dose recovered in the urine and faeces. Glucuronidation was identified as the primary route of metabolism, with the major glucuronide metabolite, M28, accounting for 57.5% of the total drug‐derived exposure and 59.7% of the administered dose recovered in urine. Conclusions: Navoximod was well tolerated, quickly absorbed and showed moderate bioavailability, with minimal recovery of the dose as unchanged parent in the urine and faeces. Metabolism was identified as the primary route of clearance and navoximod glucuronide (M28) was the most abundant metabolite in circulation with all other metabolites accounting for <10% of drug‐related exposure.